Twitter: The effect of democratic leadership towards social equality in Malaysia / Muhammad Amirul Aiman Mohd Johar ... [et al.] - Mohd Johar, Muhammad Amirul Aiman; Aliff Raziuddin, Sarah Sofea; Shahroom Amir, Nur Anisah; Azharim, Jazmina
This research paper is focuses on the effect of democratic leadership towards social equality on Twitter in Malaysia. We chose this topic because we want to research on the effect of the usage of Twitter towards the democratic leaders and the citizen of Malaysia. This research studies the perception of Twitter users towards democratic leaders. Besides that, we also want to investigate the causes of the democratic leadership practice on Twitter. Finally, we want to find out effect of democratic leader on twitter towards social equality of Malaysian citizen. From the findings, we analysed that democratic leaders does affect social equality on Twitter. For this study, we have used qualitative research whereby in-depth interviews with five informants is conducted based on our purposive sampling as methodology.